Cultural Practices and Environment along the Bishnumati River in Kathmandu (Geographical Journal of Nepal, 2009)
The Bishnumati River is one of the major sources of water in Kathmandu city for domestic and agricultural uses. But the quality of the river environment has been degraded seriously since the last few years. This paper is an attempt to explore environmental condition along the Bishnumati River with specific focus on human activities, perception and institutional efforts in dealing with the river environment. Based on field observation, household survey, and key informant survey in eight segments along the river stretch from the city periphery to down town, the information acquired indicate that human activities related to environmentally sensitive phenomena were very much dominant in degrading the river environment. The local inhabitants were aware of the river environmental conservation. The local public agencies were however not seriousness in implementing the waste management activities, but instead they practiced environmentally sensitive activities at the riverbanks. Efforts at both local community and public agencies levels are most warranted to protect the Bishnumati river environment from further degradation. The Geographical Journal of Nepal, Vol. 7, 2009: 53-60